Managing the flow of information in the cloud environment - Gesoon J.K. Al-Abbas (Genius Journals, 2023)
Management of information flows in a cloud environment serve as an important information security mechanism. The main problem in the implementation of such a mechanism is the speed of packet switching in accordance with the given rules. The article discusses methods for monitoring and managing information flows in a cloud environment based on software defined networks(SDN). Estimates of the speed of information exchange in the framework of cloud computing are constructed. A system of procedures is discussed that makes it possible to reconfigure switching tables (ST) in accordance with current changes in the topology of network interactions in a cloud environment.
Keywords: cloud computing; management of information flows; switching tables